Formulation and Incorporation of Tomato Powder in Selected Recipes - C., Abinaya; Pl., Sridevi Sivakami (The Indian Journal of Nutrition and Dietetics, 2022)
Tomato (Solanum lycopersicum.L) a functional food (neutraceutical) contains bioactive components like carotenoids β-carotene, lycopene, vitamins C, vitamin A and tocopherol, phenolic compounds (hydrocinnamic acid), flavonoids (narigenin, rutin) and other bio active components (glycolkaloids and lectin). These bioactive components will reduce the risk of chronic degenerative diseases like cancer, cardiovascular diseases, AIDS, Alzheimer’s disease, osteoporosis, osteoarthritis and asthma. The ripened tomato contain higher amount of lycopene and it reduces the oxidative stress. It act as an anti-carcinogenic, anti-inflammatory, antioxidant, hepatoprotective, cardio protective and anti-lumen. The post harvested losses in tomatoes were estimated to be 15 and 10% at the farmers and intermediaries level respectively. The harvesting loss was found highest (6%) as compared to grading, packaging, storing and transporting. On other hand the loss of tomato were found highest for mercantile (6.3%), retailer (1.5%), due to transportation and marketing. Processing techniques will improve the shelf life of the proaduct. The demand for tomato processing usually arises from a need to preserve the product for home use, out of season to add value for extra income. The current processing techniques carried out is low temperature processing, high pressure processing, pasteurization and quality control. The basic preservation principle behind all these products is to remove water by boiling to heat the product to destroy enzymes and microorganisms and concentrate the product so that contaminating microorganism cannot re-grow. Hence the present study was carried out to formulate the tomato powder by adopting different drying process like spray drying, foam drying, cabinet drying and solar dryer. The characteristics, nutrient composition, shelf life of the tomato powder was studied, formulated tomato powder was incorporated in different selected recipes.